2016
DOI: 10.1371/journal.pone.0157099
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies of Mesenchymal Stem Cell (MSC) Administration in Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review and Meta-Analysis

Abstract: BackgroundIn the last two decades, mesenchymal stem cells (MSCs) have been pre-clinically utilized in the treatment of a variety of kinds of diseases including chronic obstructive pulmonary disease (COPD). The aim of the current study was to systematically review and conduct a meta-analysis on the published pre-clinical studies of MSC administration in the treatment of COPD in animal models.Methods and ResultsA systematic search of electronic databases was performed. Statistical analysis was performed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 56 publications
2
50
1
5
Order By: Relevance
“…Following this concept, regenerative processes of the upper and lower airways may also involve stem cells. Indeed, the current literature implies stem cells to be involved in regenerative processes in lower airways . In the lung, different populations of epithelial cells function as adult stem cells, defined by their self‐renewal properties and phenotypic changes in response to tissue damage .…”
Section: Airway Stem/progenitor Cellsmentioning
confidence: 99%
“…Following this concept, regenerative processes of the upper and lower airways may also involve stem cells. Indeed, the current literature implies stem cells to be involved in regenerative processes in lower airways . In the lung, different populations of epithelial cells function as adult stem cells, defined by their self‐renewal properties and phenotypic changes in response to tissue damage .…”
Section: Airway Stem/progenitor Cellsmentioning
confidence: 99%
“…6 One critical barrier to effective MSC therapy is their insufficient homing capability to tissues of interest, especially when MSCs are infused through the vascular route. 7 Many factors contribute to the inefficient migration of these cells, among which low surface receptors' level is of high importance. 8 Some studies have highlighted that chemokine/-chemokine receptor interactions influence stem cell recruitment to the desired target, but to the best of our knowledge none of them have investigated whether hypoxia improves the migration of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The doses will require further adjustments as well as the mode of drug delivery. Previously other treatments like vitamin C 28 , angiotensin receptor blockade 29 , stem cells 30 have attenuated cigarette smoke-induced emphysema in animals. Many other studies suggested statins 31 to be an effective treatment.…”
Section: Fig 6: Neutrophil Counts and Lymphocyte Counts From Balfmentioning
confidence: 99%